2022
DOI: 10.47191/ijmra/v5-i8-42
|View full text |Cite
|
Sign up to set email alerts
|

Small Side Game: Effectiveness of Increasing Futsal Passing

Abstract: This study aimed to determine the effect of small-sided game training on passing skills. This type of research is experimental. The population used is the female futsal athletes of Parda Sleman, totaling 20 people. Instruments to determine the ability to pass using tests of passing and controlling the ball (passing-controlling). The small-sided game exercise was carried out for 18 meetings. The results showed a significant effect of small-sided game training on passing skills, with an increase of 14.55%. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Based on previous research, it was revealed that the small side games training method had a significant effect on passing skills with an increase of 14.55%. This research can be useful and can be used as additional material for training studies in football games and passing skills as a basis for making training programs to improve player performance, as well as providing theoretical and practical evidence for coaches (Walid Djaba, 2022). This is also reinforced by the opinion that the method of small side games and coordination exercises can increase aerobic endurance.…”
Section: Discussionmentioning
confidence: 83%
“…Based on previous research, it was revealed that the small side games training method had a significant effect on passing skills with an increase of 14.55%. This research can be useful and can be used as additional material for training studies in football games and passing skills as a basis for making training programs to improve player performance, as well as providing theoretical and practical evidence for coaches (Walid Djaba, 2022). This is also reinforced by the opinion that the method of small side games and coordination exercises can increase aerobic endurance.…”
Section: Discussionmentioning
confidence: 83%
“…However, increasing passing can also increase VO 2 max because players must keep moving throughout the game [49]. Small-sided game training is a good training method to improve the ability of athletes by modifying the rules and reducing the size of the field so that players will continue to be involved in the game they can improve their passing skills [50], [51].…”
Section: Discussionmentioning
confidence: 99%